MODEL DINAMIKA PENYEBARAN DBD DENGAN MENERAPKAN TIGA STRATEGI PENGENDALIANNYA - ., Kartono; Djuwandi, Djuwandi; ., Farikhin (MATEMATIKA, 2014)
The information of the dynamic of dengue fever is needed to build the model of its controlling strategy. Therefore, this research is aimed to develop a mathematical model such that the effectiveness of several controlling strategy for example 3M campaign, treatment to the infected people, andthe applying ofinsecticide can be evaluated. This mathematical model is constructed by classifying the human population into three class that are Suspectible (S), Infected (I) and Removed (R) while the vector population (aedes aegypti mosquito) is assumed belongs to the Infected (I) class. The effectiveness of the controlling strategy is analyzed using maximum Pontryagin principle. The result of this analysis shows that the 3M campaign affects the size of the suspect population.